What drives market structure? On the relation between firm demographic processes, firms? innovative behaviour and market structure - Emmanuelle Fauchart; Max Keilbach (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2002)
In this paper we suggest an structural model that specifies firm growth as a function of firm specific parameters and of competition for purchase power with other firms on a given market. Moreover, we explicitely model firms? innovative behaviour and distinguish between dierent innovation regimes. On the basis of a set of simulations of this model we derive a number of empirically testable hypotheses. A subset of these have already found support in the empirical literature. We take these as evidence in favour of the explanatory power of the model. In addition, we are able to derive further testable propositions on the interaction of firm-demographic processes, in-novative behaviour and market structure that go beyond the existing literature and that we suggest for further research. We conclude that the approach chosen here provides a fruitful pathway for further research.
Keywords: L60; O30; G30; 330; Firm size distribution; innovation regime; technological regime; industrial dynamics; firm demography; carrying capacity; market concentration; Innovation; Unternehmensentwicklung; Industrielle Forschung; Marktstruktur; Betriebsgrößenstruktur; Simulation; Theorie